Konstruksi Berita Kasus Penembakan Enam Laskar FPI pada Tempo.co - Vicky Pratama Putra (Neolectura, 2022)
The shooting incident that occurred between members of the Islamic Defenders Front (FPI) and the police caused the death of six members of the Soldiers, which became an interesting national issue to be reported on, because from the beginning of this case there were two versions released by both parties involved so that the media would construct their reality through what they see. The construction itself is part of the framing or media frame based on ideology, political views, and the vision and mission of the media itself and can be seen through the use of language as a highlight of meaning. This became the basis for a research entitled